FRIEND OR FOE? INTER‐AGENCY COOPERATION, ORGANIZATIONAL REPUTATION, AND TURF. (23rd March 2015) - BUSUIOC, E. MADALINA
Abstract : This article aims to explain two contrasting cases of bureaucratic cooperation: the cooperation practices of two similar European agencies – Europol and Frontex – with corresponding national‐level structures. To understand why cooperation has proceeded smoothly in one case (border management), while triggering strong turf‐protective tendencies in the other (law enforcement), the article develops a theoretical approach to cooperation that is both 'turf' and reputation sensitive. Drawing on a variety of documents and interview material, the article demonstrates that the divergent outcomes are shaped to a large extent by the different reputational impact of cooperation for the national authorities concerned. In one case, cooperation depletes important reputational resources of national authorities, threatening their 'reputational uniqueness' and triggering turf‐protective tendencies. In the other, vertical and horizontal cooperation efforts bring important gains to national authorities' ability to discharge their tasks successfully and, thus, to their reputation‐building efforts. Crucially however, they do so without threatening their 'reputational uniqueness'.